Ko-volume change characteristics of an unsaturated soil with respect to various loading paths - Rahardjo, Harianto (2011)
The volume change behavior of an unsaturated soil is a function of the stress state variables; namely, net normal stress and matric suction. The total and water volume changes during drained and constant water content loadings are investigated, and their behavior is described with respect to changes in the stress state variables. Volume changes are also presented in terms of void ratio and water content changes. The differing characteristics of volume change during drained and constant water content loadings are reflected clearly through the void ratio and water content changes. The significance of the highest, past matric suction is shown to be similar to the preconsolidation pressure influence on a saturated soil. The laboratory test results show that the water coefficient of volume change changes significantly from the reloading curve to the virgin compression curve. The effect of preconsolidating the soil was also shown to influence significantly the measured soil-water characteristic curve.